Shared Religious Education through Christian–Islamic Team Teaching - Gmoser, Agnes 1992-; Kramer, Michael; Mešanović, Mevlida; Weirer, Wolfgang 1963-; Wenig, Eva; Yağdı, Şenol (2024)
The article, which is written by an interreligious team, provides comprehensive insights into the conception, implementation and accompanying research of a project on Christian–Islamic religious education in team teaching. The aim of the project is to expand the denominational religious education lessons anchored in Austrian schools through religious-cooperative units taught jointly by a Christian and an Islamic teacher. The analysis of the teaching units is carried out in the format of design-based research and thus encompasses numerous aspects of interreligious educational processes, which are examined in this article. Firstly, the design of the project is described and the legal framework associated with it is explained in the context of the Austrian school system. Subsequently, learning requirements on the part of Christian and Muslim pupils are presented, with a particular focus on their preconceptions and attitudes towards religion in general as well as other religions. Special attention is paid to the specific framework conditions of Islamic religious education teachers, which differ in many aspects from those of Catholic religious education teachers. Furthermore, interreligious competences they consider necessary are described. Specific insights into the teaching units and the complementary research provide information about the opportunities and challenges of interreligious education in team teaching by two teachers. After this focus on the teachers, an outline of the students’ perspectives on the teaching units completes the presentation of the research results. In the concluding summary, the local theories developed from the overall project are presented and discussed.
Keywords: design-based research; Muslims; Christians; Religious Education; Team teaching; Interfaith Dialogue; Interreligious Learning